Increasing basal nitrogen fertilizer rate improves grain yield, quality and 2-acetyl-1-pyrroline in rice under wheat straw returning - Wang, Jun; Qiu, Yuanyuan; Zhang, Xingyu; Zhou, Zhou; Han, Xian; Zhou, Yang; Qin, Li; Liu, Kun; Li, Siyu; Wang, Weilu; Chen, Yun; Yang, Jianchang; et al. (Frontiers in Plant Science, 2023)
Straw returning plays an essential role in crop yields and the sustainable development of agriculture. However, the effects and mechanisms of nitrogen (N) fertilizer management on grain yield, quality and aroma substance 2-acetyl-1-pyrroline (2-AP) content under wheat straw returning are still unclear. In this field experiment, two japonica rice cultivars were used as materials, wheat straw non-returning (NS) and wheat straw full returning (WS) were designed coupled with two N application ratios, namely basal fertilizer: tiller fertilizer: panicle fertilizer =5:1:4 (local farmers' fertilizer practice, LFP) and 7:1:2 (increasing basal fertilizer rate, IBF) under the total N application rate of 270 kg ha-1. The effects of the four treatment combinations (NS-LFP, NS-IBF, WS-LFP, WS-IBF) on yield, cooking and eating quality, and 2-AP content in rice were investigated. The two-year (2020, 2021) results showed that: 1) WS-IBF significantly increased the number of panicles and grains per panicle, leading to the increase in grain yield by 6.67%–12.21%, when compared with NS-LFP, NS-IBF and WS-LFP. 2) WS-IBF enhanced the taste value, peak viscosity, breakdown value, the ratio of amylopectin to amylose, and the ratio of glutelin to prolamin while reducing the setback value and amylose content of rice flour. 3) Compared with NS, WS increased the activities of proline dehydrogenase and ornithine transaminase, the synthetic precursors of 2-AP, and finally increased 2-AP content in rice grains. WS-IBF slightly decreased 2-AP content, but there was no significant difference with WS-LFP. The above results indicated that adjusting the N regime and increasing basal N fertilizer rate under wheat straw returning is conducive to improving grain yield, cooking and eating quality, and 2-AP content in rice.